The Potential of Metarhizium anisopliae (Metsch.) Sorokīn as the Biocontrol Agent Against Cacao Pod Borer (Conopomorpha cramerella Snellen) - Mandariaga, Meljhon N.; Aceres, Larry V.; Juruena, Merlina H.; Owanes, Cristy F.; Besas, Ulysses P. (Department of Agronomy and Horticulture, IPB University, 2026)
Metarhizium anisopliae (Metsch.) Sorokīn is an entomopathogenic fungus with broad bio insecticidal potential, widely recognized for its role in sustainable pest management. This review examines the taxonomy, pathogenesis, infection symptoms, environmental requirements, host specificity, and dual role as both a biocontrol agent and an endophyte. Special emphasis is placed on its efficacy against the cacao pod borer (Conopomorpha cramerella Snellen), a significant pest in Southeast Asia that causes yield losses exceeding 50% in cacao plantations. Laboratory and semi-field studies report larval mortality rates of up to 80%–90% under controlled conditions. However, field-level efficacy varies due to environmental factors such as temperature, relative humidity, UV exposure, and soil characteristics. The review also discusses formulation strategies, including conidial suspensions and granular formulations, that improve fungal persistence and infection success. Despite promising outcomes, the effectiveness of M. anisopliae is influenced by strain variability, local adaptation, and integration with cultural practices. Understanding these dynamics is crucial for optimizing the application of this approach in integrated pest management (IPM) systems and advancing sustainable cacao production.